Analisis Risiko Karsinogenik Paparan PM10 Terhadap Pedagang di Kelurahan Pasar Jambi - Resti Ayu Lestari; Rizki Andre Handika; Solikhati Indah Purwaningrum (Universitas Andalas, 2019)
Particulate Matter 10 (PM10) is small particles with generally 10 μm diameters. These particles can be inhaled and induce respiratory system disorders, such as breathlessness, lung cancer and even death. The purpose of this study was to analyze the carcinogenic level of health risks that were caused by PM10 exposure to vendors in Pasar Jambi. This study used observational research with Environmental Health Risk Assessment approach. The element of carcinogenic level in PM10 included Pb and Ni. Primary data of this study were vendors characteristics, Pb concentration and Ni concentration. The number of samples used was 95 people. The results showed that the average concentration of Pb and Ni at Pasar Jambi were 27.938x10-3 µg/m3 and 2.574x10-3 µg/m3. The average realtime intake of Pb and Ni were 7.015x10-7 mg/kg/day and 5.477x10-8 mg/kg/day. The average lifetime intake of Pb and Ni were 2.073x10-6 mg/kg/day and 1.619x10-7 mg/kg/day. Excess Lifetime Cancer Risk (ELCR) for Pb exposure to all samples was ≤10-6, as well as for Ni exposure. In conclusion, carcinogenic risk for vendors in Pasar Jambi was uncertain and the carcinogenic level of health risk mostly safe for realtime and lifetime.Keywords : PM10, Carcinogenic, Risk Assessment, Health ABSTRAK Particulate Matter 10 (PM10) adalah partikel kecil yang umumnya berdiameter ≤ 10 μm. Partikel-partikel ini dapat dihirup dan menyebabkan gangguan sistem pernapasan, seperti sesak napas, kanker paru-paru dan bahkan kematian. Tujuan dari penelitian ini adalah untuk menganalisis tingkat risiko kesehatan karsinogenik yang disebabkan oleh paparan PM10 terhadap pedagang di Pasar Jambi. Penelitian ini menggunakan pendekatan Analisis Risiko Kesehatan Lingkungan. Unsur tingkat karsinogenik dalam PM10 adalah Pb dan Ni. Jumlah sampel yang digunakan adalah 95 orang. Hasil penelitian menunjukkan bahwa konsentrasi rata-rata Pb dan Ni di Pasar Jambi adalah 27,938x10-3 μg/m3 dan 2,574x10-3μg/m3. Asupan Pb dan Ni rata-rata realtime adalah 7,015x10-7mg/kg/hari dan 5,477x10-8 mg/kg/hari. Asupan Pb dan Ni rata-rata seumur hidup adalah 2,073x10-6 mg/kg/hari dan 1,619x10-7mg/kg/ hari. Excess Lifetime Cancer Risk (ELCR) untuk paparan Pb dan Ni untuk semua sampel adalah ≤10-6. Kesimpulannya, risiko karsinogenik bagi pedagang di Pasar Jambi masih aman dan belum berdampak karsinogenik.Kata Kunci : PM10, Karsinogenik, Analisis Risiko, Kesehatan